Kondycja posthistoryczna. Rzecz o telewizji, nowych mediach i polityce - Wiatr, Przemysław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
In the text, the author deals with extensive issues of media-politics relations. Using the conceptual apparatus developed by Vilém Flusser, he shows through specific examples (the Romanian revolution, the presidential elections in the United States) the transformations in the social imagination that have occurred as a result of technological changes – primarily the transition from “television reign” to “taking control” by the so-called new media. He also looks to the future, forecasting how an autonomous technology (e.g. artificial intelligence) may soon further complicate the social and political context of the contemporary times.